2011
DOI: 10.1186/1756-0500-4-225
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of five candidate genes within the ETEC F4ab/ac candidate region in pigs

Abstract: BackgroundEnterotoxigenic Escherichia coli (ETEC) that express the F4ab and F4ac fimbriae is a major contributor to diarrhoea outbreaks in the pig breeding industry, infecting both newborn and weaned piglets. Some pigs are resistant to this infection, and susceptibility is inherited as a simple dominant Mendelian trait. Indentifying the genetics behind this trait will greatly benefit pig welfare as well as the pig breeding industry by providing an opportunity to select against genetically susceptible animals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…In addition to MUC13 , two other genes, encoding structurally similar cell surface mucins and also located on Chr13, are known to be expressed in porcine jejunum: MUC4 and MUC20 [3]. To identify whether there is interaction between MUC13 or ITGB5 with each of the two mucin genes, we firstly separately compared the mRNA expression levels of MUC4 and MUC20 in ITGB5 - or MUC13 -deficient cells with that in the negative control cells at 44 h post-transfection of siRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to MUC13 , two other genes, encoding structurally similar cell surface mucins and also located on Chr13, are known to be expressed in porcine jejunum: MUC4 and MUC20 [3]. To identify whether there is interaction between MUC13 or ITGB5 with each of the two mucin genes, we firstly separately compared the mRNA expression levels of MUC4 and MUC20 in ITGB5 - or MUC13 -deficient cells with that in the negative control cells at 44 h post-transfection of siRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…As both ITGB5 and MUC13 are candidate genes for ETEC F4ac receptor [3], [11], we finally assessed the influences of these two genes on adhesion of F4ac ETEC to the piglet small intestinal epithelial cells (Figure 4). IPEC-J2 cells were separately transfected with ITGB5 - or MUC13 -targeting siRNA for 48 h, and the cells were co-cultured with live bacteria for a further 3 h. Quantitative real-time PCR was used to measure the counts of adherent bacteria as described previously [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S.typhimurium -infected pigs show reduced MUC4 expression on the surface of colonic epithelium compared with non-infected pigs, indicated that MUC4 is important in inflammatory response in colonic tissues [12]. Previously, we and other investigators reported MUC4 polymorphisms that were strongly associated with susceptibility to enterotoxigenic Escherichia coli (ETEC) F4ab/ac in pigs [13,14], although we recently demonstrated that susceptibility towards ETEC F4ac is governed by the MUC13 gene proximal to MUC4 (unpublished data). More recently, a variant in MUC4 has been evidenced to be significantly associated with prolificacy traits; MUC4 expression levels in the uterine of high prolific sows are two-fold greater than those in low prolific sows [15].…”
Section: Introductionmentioning
confidence: 99%
“…that the polymorphisms are not the causative mutations, but are good markers, and more accurate markers for F4acR than for F4abR [31]. Jacobsen et al also found one MUC20 -g.2387C>T SNP that perfectly matched the F4ab/acR phenotype in four tested animals, two resistant Wild Boars and two homozygous susceptible Large White [32]. However, genotyping of 42 additional animals of different breeds showed that this SNP is not associated with the phenotype of ETEC-F4ab/ac susceptibility [32].…”
Section: Genetic Research On F4 Receptors – the Positional Candidamentioning
confidence: 99%